2018
DOI: 10.1016/j.jaci.2017.04.041
|View full text |Cite
|
Sign up to set email alerts
|

The TH1 phenotype of follicular helper T cells indicates an IFN-γ–associated immune dysregulation in patients with CD21low common variable immunodeficiency

Abstract: Identification of excessive IFN-γ production by blood and lymph node-derived T cells of patients with CVID with immune dysregulation will offer new therapeutic avenues for this subgroup. CD21 B cells might serve as a marker of this IFN-γ-associated dysregulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
96
6
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(117 citation statements)
references
References 60 publications
9
96
6
3
Order By: Relevance
“…As explained earlier, TFH can be divided into two subsets: the non-efficient helper TFH1 and the efficient helpers TFH2 and TFH17. Interestingly, we (75) and others (77,78,80) highlight a specific increase of the circulating TFH1 only in non-infectious CVID patients. Moreover, CXCR3 + (75) or Tbet + (78) cells were amplified in secondary lymphoid organs of CVID patients, suggesting that the blood observations reflect the GC counterpart.…”
Section: Tfh and Cvidsupporting
confidence: 50%
See 2 more Smart Citations
“…As explained earlier, TFH can be divided into two subsets: the non-efficient helper TFH1 and the efficient helpers TFH2 and TFH17. Interestingly, we (75) and others (77,78,80) highlight a specific increase of the circulating TFH1 only in non-infectious CVID patients. Moreover, CXCR3 + (75) or Tbet + (78) cells were amplified in secondary lymphoid organs of CVID patients, suggesting that the blood observations reflect the GC counterpart.…”
Section: Tfh and Cvidsupporting
confidence: 50%
“…Interestingly, our group (75) and others (76)(77)(78) observed an increase of circulating TFH (memory CXCR5 + CD4 T cells) in CVID patients harboring non-infectious complications. Moreover, TFH expressing PD-1 were present at higher levels in CVID patients with complications (75)(76)(77)(78). Patients classified as smB − based on the EUROClass have <2% of switched memory B cells among circulating CD19 + cells (12).…”
Section: Tfh and Cvidmentioning
confidence: 71%
See 1 more Smart Citation
“…The excessive IL-12 production we have seen in our patients seems to be clinically relevant since this was associated with skewing of helper T cells towards a predominantly Th1 phenotype. A recent study in CVID patients showed that skewed Th1 phenotype of follicular helper cells was associated with immune dysregulation and inflammatory complications [32]. We used findings from our study to select a targeted therapy for one of the patients (P16) with several inflammatory complications (granuloma role of IL-12).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, several abnormalities in immune cells' counts and function, in different combinations and in association with specific clinical features, have been described in CVID patients. Among these, the reduction of class-switched memory B cells and/or plasmablasts (9,10), the expansion of transitional B cells and/or CD21low B cells (11,12), the reduction of naive T cell and/or Treg cell, and the increase of peripheral blood T FH cells (13,14), are the most remarkable.…”
Section: Introductionmentioning
confidence: 99%